If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -1 + -4y + 8 = 0 Reorder the terms: -1 + 8 + 10y + -4y = 0 Combine like terms: -1 + 8 = 7 7 + 10y + -4y = 0 Combine like terms: 10y + -4y = 6y 7 + 6y = 0 Solving 7 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6y = 0 + -7 6y = 0 + -7 Combine like terms: 0 + -7 = -7 6y = -7 Divide each side by '6'. y = -1.166666667 Simplifying y = -1.166666667
| 10-2b-3b=20 | | 3(x-2)-(x+6)=4(x-1) | | (2(x^2)+2)= | | (4y)(4y)= | | (M^0)(-4)= | | 3+2(x-7)=x-18 | | 24a^4-4a^4= | | -(u-w)-6(-3w-6u)= | | 6x^6-60x^5-144x^4= | | 45x-5=546 | | 6(3z-1)-5(z+5)=10(z+1) | | 5(z-4)+4z=5-6z | | 3x^2-25x+36=0 | | O(9)=2(9)-1 | | x^2=-112 | | 7-2y=11-6y+4y | | 2x+5y=-2 | | 3x+4+x-10=2+x-4 | | -22=4x | | 12y-5y=39+4y | | 2x+4+8x-1=18 | | 0=4x^3+.808x^2-.000000000185 | | 4x-1.3=8.7 | | (5/3)x=-70 | | 4a-9=3(a-3) | | 2x+23=4(x+5) | | 4a-9=3(a-9) | | x+2.3=4.1 | | (6x-5)/4=3 | | 3r+6=48+11r | | 5c-6=-9 | | 12-8-3= |